The Role of Self-Efficacy, Expectations and Perceived Organizational Support: How Employability of Yogyakarta Print Media Employees - Alfareza Hairyanto Arman; Khoiruddin Basori; Fatwa Tentama (Psikostudia : Jurnal Psikologi, 2023)
Unemployment is a huge and crucial problem today. Which has an impact on decreasing people's income to reduce the level of prosperity, as well as the emergence of anxiety and stress about the future. Related to this, the purpose of this study is to determine the role of self-efficacy, expectations, and Perceived Organizational on Employability in Yogyakarta Print Media Employees. From this objective, the researcher hypothesizes that significant value on the role of self-efficacy, hope, and perceived organizational support on employee employability. This study used a quantitative survey method, with a sample of employees working in five print media companies located in Yogyakarta (n=90). The five companies include Harian Jogja, Kedaulatan Rakyat, Radar, Republika and Tribun Jogja. The sampling technique used purposive sampling, with the help of data collection through a scale of self-efficacy, expectations, perceived organizational support and employability. The Employability scale has three dimensions including career identity, personal adaptability, and human and social capital. The self-efficacy scale has three dimensions including magnitude, strength, and generality. Then the hope scale includes goals, pathways, and agency. Meanwhile, the perceived organizational support scale has three dimensions including fairness, supervisor support, and organizational rewards & job conditions. The data obtained were analyzed using multiple regression analysis techniques. The results obtained prove that self-efficacy, expectations, and perceived organizational support have a very significant role in employability. Self-efficacy helps strengthen motivation and positive expectations of the work environment so that it can perceive company support as one of the intrinsic factors that make it survive and adapt to problems in the company.Pengangguran sangat banyak dan menjadi masalah krusial saat ini. Yang berdampak pada menurunnya pendapatan masyarakat sehingga menurunkan tingkat kemakmuran, serta munculnya kecemasan dan stres mengenai masa depan. Terkait hal tersebut, maka tujuan penelitian ini adalah untuk mengetahui Peran Efikasi Diri, Harapan dan Perceived Organizational terhadap Employability pada Karyawan Media Cetak Yogyakarta. Dari tujuan ini, peneliti berhipotesis bahwa nilai signifikan pada peran efikasi diri, harapan dan perceived organizational support terhadap employability karyawan. Penelitian ini menggunakan metode kuantitatif survey, dengan sampel karyawan yang bekerja di lima perusahaan media cetak yang berada di Yogyakarta (n=90). Lima perusahaan tersebut diantaranya Harian Jogja, Kedaulatan Rakyat, Rada, Republika dan Tribun Jogja. Teknik pengambilan sampel menggunakan purposive sampling, dengan bantuan pengumpulan data melalui skala efikasi diri, harapan, perceived organizational support dan employability. Skala Employability memiliki tiga dimensi diantaranya career identity, personal adaptability dan human and social capital. Skala efikasi diri memiliki tiga dimensi diantaranya magnitude, strenght dan generality. Kemudian skala harapan diantaranya goal, pathways dan agency. Sedangkan untuk skala perceived organizational support memiliki tiga dimensi diantaranya fairness, supervisor support, dan organizational reward & job condition. Adapun data yang diperoleh dianalisis dengan teknik analisis regresi berganda. Hasil yang diperoleh membuktikan bahwa efikasi diri, harapan dan perceived organizational support mempunyai peran yang sangat signifikan terhadap employability. Efikasi diri membantu menguatkan motivasi dan harapan positif pada lingkungan kerja sehingga mampu mempersepsikan dukungan perusahaan sebagai salah satu faktor intrinsik yang membuatnya bertahan dan beradaptasi dengan masalah di perusahaan.